2000
DOI: 10.1034/j.1600-051x.2000.027003212.x
|View full text |Cite
|
Sign up to set email alerts
|

Plaque removal by worn toothbrush

Abstract: Each individual is capable of maintaining low PI, even if using a toothbrush that shows evidence of wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
40
4
13

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 16 publications
9
40
4
13
Order By: Relevance
“…Worn toothbrush is known to be less effective in plaque removal and control of gingivitis (29). On the contrary, there are reports showing that wear status of a toothbrush may not be critical in ensuring plaque control (30, 31). Although there is no brushing technique that is superior to others in plaque removal, the horizontal technique that is commonly practiced in this study population, together with the dentifrices claimed to enhance plaque removal (due to presence of abrasive particles), could have resulted into a better oral hygiene standards, but unfortunately this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Worn toothbrush is known to be less effective in plaque removal and control of gingivitis (29). On the contrary, there are reports showing that wear status of a toothbrush may not be critical in ensuring plaque control (30, 31). Although there is no brushing technique that is superior to others in plaque removal, the horizontal technique that is commonly practiced in this study population, together with the dentifrices claimed to enhance plaque removal (due to presence of abrasive particles), could have resulted into a better oral hygiene standards, but unfortunately this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Also, surveys of dental professionals have found that the majority identify splayed bristles as the main sign of toothbrush wear and recommend replacement of manual brushes every 2–3 months (Abraham et al 1990, Daly & Marshall 1996, Daly et al 2000). However, growing evidence from more recently published studies indicates that the wear status of a manual toothbrush may not be critical in effective plaque removal (Daly et al 1996, Sforza et al 2000, Tan & Daly 2002). In these studies, there was no difference in efficacy of plaque removal between new brushes and brushes that had been used routinely at home for periods of 9–12 weeks.…”
mentioning
confidence: 99%
“…Целью чистки зубов является удаление биопленки и уменьшение количества патогенных микроорганизмов [22,78,90]. Во время чистки зубов щеткой удаление зуб-ного налета достигается прежде всего благодаря прямому контакту между волокнами зубной щетки и поверхностя-ми зубов и мягких тканей [70].…”
Section: стоматология 2 2015unclassified
“…Sforza, L. Hogan, L. Wambier также не связывают степень износа щетки с ухудшением удаления зубного на-лета [45,78,92]. Они полагают, что значительно большее влияние на качество гигиены рта оказывают техника и продолжительность чистки зубов, а также сила давления на зубы в процессе чистки.…”
Section: эффективность зубной щетки в зависимости от степени износаunclassified
See 1 more Smart Citation